PERENCANAAN PEMANFATAN LAHAN DALAM INVESTASI SEKTOR PARIWISATA: (Studi Perencanaan Pemanfatan Lahan Pemerintah di Kabupaten Kaimana Provinsi Papua Barat) - Abdullah Remon Sirfefa (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
This study aims to describe, explain, analyze and provide an understanding of land use planning belonging to the government of Kaimana Regency, West Papua Province. Research using descriptive qualitative method. The results of this study where there is no plan from the government kaimana to take advantage of the potential of the existing area in the form of land or land assets. Regional apparatus organizations tend to wait for orders or instructions from regional leaders. Therefore the author conveys several steps that need to be taken by the Kaimana Government in utilizing their vacant land as follows: Cleaning and Fencing, Construction of access roads, Construction of city parks, Development of cultural parks.